Fashion Figures - Borza, Melissa A. (Springer Nature, 2017)
STEM careers; girls; preteen; YA; mathlete; fashionista; math; middle school
English
Keywords: Research & information: general; Education; Mathematics & science; STEM careers; girls; preteen; YA; mathlete; fashionista; math; middle school